2022
DOI: 10.1371/journal.pone.0278072
|View full text |Cite
|
Sign up to set email alerts
|

Drug utilization patterns before and during COVID-19 pandemic in Manitoba, Canada: A population-based study

Abstract: Background The COVID-19 pandemic has led the Canadian provincial governments to take unprecedented measures, including restrictions to healthcare services and pharmacists. Limited evidence exists on changes in prescription trends in Canada during the pandemic period. Objectives To examine the trend of prescription medications’ utilization before and during COVID-19, among incident and prevalent users in the general population. We examined 18 major classes of medications. Methods We used the administrative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…Different jurisdictions in Canada have reported changes in medication use during the early periods of the pandemic, with a significant increase in claims for some drugs (e.g., cardiovascular drugs and oral antidiabetic drugs) but a slight decrease in claims for controlled drugs such as opioids and benzodiazepines ( 16 ). Similar changes in chronic medication use due to the COVID-19 pandemic have been observed in other parts of the world ( 3 , 4 , 10 , 12 14 ). For example, a study from eight European countries reported a decrease in antibiotics, COPD, and asthma medication ( 26 ).…”
Section: Discussionsupporting
confidence: 69%
“…Different jurisdictions in Canada have reported changes in medication use during the early periods of the pandemic, with a significant increase in claims for some drugs (e.g., cardiovascular drugs and oral antidiabetic drugs) but a slight decrease in claims for controlled drugs such as opioids and benzodiazepines ( 16 ). Similar changes in chronic medication use due to the COVID-19 pandemic have been observed in other parts of the world ( 3 , 4 , 10 , 12 14 ). For example, a study from eight European countries reported a decrease in antibiotics, COPD, and asthma medication ( 26 ).…”
Section: Discussionsupporting
confidence: 69%
“…In contrast, the drug use of outpatients with Medicaid by Elizabeth Williams experienced a decrease of 3% in the drug utilization of cardiac drugs in COVID-19 period (2020) compared to the pre-COVID-19 period (2019) [34]. However, with the influence of COVID-19 restrictions and curfew, a study by Aboulatta et al in Canadian citizens noted a sharply decline in the consumption of cardiovascular drugs in incident users of -23.05% immediately after enacting COVID-19 restriction, followed by a rebound increase monthly, while in prevalent users only observed a gradual drop monthly in the use of cardiovascular drugs [16].…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 has disrupted both individual visits and access to medical prescriptions from outpatient services at hospitals, which caused many disadvantages in regards to worsen symptoms of chronic diseases [4,[12][13][14]. Several studies have examined the impact of COVID-19-related restrictions on drug utilization among outpatients, revealing fluctuations in the prescription patterns for chronic conditions [15][16][17]. However, there is a limited body of research focusing on the elderly population, who require special attention due to their high prevalence of chronic diseases and comorbidities, making them particularly vulnerable to the effects of the pandemic [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the effect of the pandemic on initiation of antidiabetic drugs, there are few studies and most indicate some significant impact on drug use [19][20][21]. A considerable decrease in the number of weekly insulin prescription fills was seen during, compared to before, the COVID-19 pandemic in the US (January 2019 and October 2020) [21], and lower rate of treatment initiations with antidiabetic drugs during lockdown and an increasing rate in treatment disruptions afterward was reported in France [20].…”
Section: Introductionmentioning
confidence: 99%
“…A considerable decrease in the number of weekly insulin prescription fills was seen during, compared to before, the COVID-19 pandemic in the US (January 2019 and October 2020) [21], and lower rate of treatment initiations with antidiabetic drugs during lockdown and an increasing rate in treatment disruptions afterward was reported in France [20]. Furthermore, a temporary but statistically significant immediately decrease in antidiabetic drugs initiation at the beginning of the pandemic, followed by a significant increase in slope, was reported in Canada during the first and second quarters of the pandemic [19].…”
Section: Introductionmentioning
confidence: 99%